Race, ethnicity, gender and other social characteristics as factors in health and health care disparities - Kronenfeld, Jennie Jacobs (Research in the sociology of health care ;, 2020)
The contributors to this latest volume of Research in the Sociology of Health Care investigate race, ethnicity and gender as factors in health and health care disparities. Looking specifically at the factors that impact race and ethnicity in a US context, gender issues, hospitals and health care spending, and research from India. Chapters focus on linkages to health disparities among races, health experiences for incarcerated women and issues of hospital and health care spending.